Implementasi Program Sedekah Sampah Sebagai Model Pengelolaan Sampah di Sekolah - Insren Loisa Marsyom; Angel Ribka Chalista; Virrela Desvinta Ayu Nur Azizah; Gischa Natasya; Rizky Eka Putri; Ani Apriani (Institut Teknologi Nasional Yogyakarta, 2024)
Waste management issues in schools are often overlooked, even though they can negatively impact the environment and health. The Sedekah Sampah program at SD IT Salsabila Baiturrahman aims to address waste problems while providing economic benefits for the school. The methods used include education, actions involving collection, sorting, and selling, and finally, evaluation. The evaluation was conducted by distributing questionnaires to parents and teachers before and after the implementation of the Sedekah Sampah program. The results show a significant increase in the knowledge, attitudes, and behavior of school members regarding waste management, as indicated by the significance value in the statistical test using a paired sample test of 0.000 (less than 0.05). This increase aligns with previous studies emphasizing the importance of education and active participation in waste management. The program also successfully raised funds from waste management, which were used to support school activities. The significance of these results lies in the success of turning waste into a valuable economic resource and raising environmental awareness among students, teachers, and parents.